Histological Evidence of Increased Osteoclast Cell Number and Asymmetric Bone Resorption Activity in the Tibiae of Interleukin-6-Deficient Mice. (August 2014) - Liu, Hongrui; Feng, Wei; Yimin,; Cui, Jian; Lv, Shengyu; Hasegawa, Tomoka; Sun, Bao; Li, Juan; Oda, Kimimitsu; Amizuka, Norio; Li, Minqi
Interleukin-6 (IL-6) is a multifunctional cytokine considered to modulate bone homeostasis. Based on previous contradictory studies, we aimed to verify the influence of IL-6 deficiency on bone remodeling using an IL-6 knockout (IL-6-/-) murine model. Eight-month-old male mice, homozygous for the disrupted IL-6 gene, and their wild type (WT) littermates (control), were used. After transcardiac perfusion, tibiae were removed for histochemical analysis. Compared with the control group, IL-6 deficiency increased tartrate resistant acid phosphatase (TRAP)-positive osteoclast numbers and up-regulated the alkaline phosphatase (ALP) activity of osteoblasts in the metaphysis of the tibia. However, further analysis of serial histological sections from IL-6-/- mice found a significant discrepancy in osteoclast number, with the higher number of TRAP-positive osteoclasts conflicting with the lower number of cathepsin K-positive osteoclasts. Moreover, TUNEL staining identified a significantly higher rate of osteoclast apoptosis in IL-6-/- mice as compared with their WT controls. IL-6 deficiency induced abundant TRAP-positive osteoclasts but delayed bone remodeling by significantly inhibiting the bone resorption activity of osteoclasts and promoting osteoclast apoptosis.